The Magnus effect and the American football - Guzman, C.; Brownell, C.; Kommer, E. M. (Sports Engineering, 2016)
The aerodynamics of an American NFL football during an end over end kick were investigated utilizing a custom rotating apparatus and large-scale wind tunnel. Non-rotating lift and drag coefficients were measured and agree well with previous data from other athletic balls and a smooth sphere. The rotation effect on an American football increased both the lift and drag coefficients more dramatically than what has been seen with symmetrical objects over a wide range of rotational rates. The results from this study can be used to more accurately predict the flight trajectory of an end over end kick, and help optimize the balance between kick velocity and rotational speed for a given kicker`s leg strength.